High Frequency of Multidrug-Resistant (MDR) Atypical Enteropathogenic Escherichia coli (aEPEC) in Broilers in Hungary - Adorján, András; Makrai, László; Mag, Tünde; Jánosi, Szilárd; Könyves, László; Tóth, István (Frontiers in Veterinary Science, 2020)
Escherichia coli (EC) strains belong to several pathotypes capable of infecting both humans and animals. Some of them have zoonotic potential and can sporadically cause epidemic outbreaks. Our aim was to screen for the distribution of these pathotypes in broilers and their related products. Therefore, E. coli strains were isolated (n=118) from poultry intestine (n=57), carcass (n=57) and wastewater (n=4) samples from one slaughterhouse with own reared poultry source and the National Reference Laboratory (NRL) poultry E. coli collection (n=170) from the year 2017 was also studied. All 288 E. coli strains were screened by PCR for pathotype-specific genes stx, eae, st-lt, aggR, ipaH and for further EPEC-specific virulence genes (bfp, EAF, tir, perA, ler). Altogether 35 atypical enteropathogenic E. coli (aEPEC) strains from the slaughterhouse and 48 aEPEC strains from the NRL collection were found. Regarding the phylogenetic groups of aEPEC, all four main groups were represented but there was a shift towards the B2 group (25%) as compared with the non-EPEC isolates (3%). The aEPEC isolates belonged to serogroups O14, O108 and O45. Multidrug resistance (MDR) was abundant in aEPEC strains (80 out of 83 aEPEC) with a diverse resistance pattern (n=56). Our results of this study indicate that the high frequency of aEPEC in broilers and on their carcass surface, with frequent MDR to several antibiotic groups, raises the possibility that these strains pose a zoonotic risk to humans.